HUBUNGAN KELENGKAPAN INFORMASI DENGAN PEMAHAMAN TENTANG PERSETUJUAN TINDAKAN MEDIS DI RUMAH SAKIT UMUM KELAS C SE-KOTA PEKANBARU - Doni Jepisah, Tri Purnama Sari, (Menara Ilmu, 2019)
Based on Act No. 29 years 2004 about medical practice as stated in articles 45paragraphs (1) said that informed consent is approval of medical action which is givenby the patient or his immediate family after obtaining a complete explanation aboutmedical or dentist action that will be performed on that patient. This research aims tofind out the relationship between the completeness information with an understanding ofthe approval of medical action in public hospital with class C at Pekanbaru. Dataanalysis was carried out in two stages: univariate and bivariate analysis. Based on theresults of research found that from 194 respondents there were 120 respondents (61.9%)who had a low level of understanding, there were 119 (63.1%) respondents who receivedincomplete information about approval of medical action. Based on the result ofbivariate analysis found that there was a significant relationship between completenessinformation (p value 0,001 or 2,857) with an understanding of the approval of medicalaction. It is recommended that the hospital with class C should conduct re-evaluate toknow whether all medical personnel who perform surgical action or other invasiveaction are in accordance with the procedure applied and given a complete information,so, if things happen that are not desirable after surgery, the patient or family is expectedto receive it because before the surgery is done, the doctor has given an explanation tothe patient.Keyword: Completeness Information, Understanding, Approval of Medical Action